PENGARUH PEMBIAYAAN RAHN DAN PEMBIAYAAN MULIA TERHADAP LABA PADA PT PEGADAIAN SYARIAH INDONESIA - Khairun Fua’dah; Zulkarnaini; Syawal Harianto (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to analyze the effect of Rahn and MULIA financing on profits at Indonesian Sharia Pawnshops. This research was conducted using secondary data obtained from the official OJK website, namely statistical data on government pawnshop companies for 2018-2022. The method used in this study is a quantitative method by analyzing quantitative data. The data collection technique for this research is to collect secondary data that has been prepared and published for public consumption. The analysis tool used is the Eviews 10 application. The results showed that the Rahn variable had a positive and insignificant effect on the profits of PT Pegadaian Syariah Indonesia in 2018-2022. Meanwhile, the MULIA variable has a negative and insignificant effect on the profits of PT Pegadaian Syariah Indonesia in 2018-2022. Based on the results of the F test, it is known that the two independent variables simultaneously have no effect on the profits of PT Pegadaian Syariah Indonesia in 2018-2022.